Impact of protein source and ammonium chloride inclusion on Boer goat growth and carcass quality - Henry, Jay R.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Research of feedlot goats has gained importance as goat consumption in the United States has increased tremendously in within recent years. In the field of goat nutrition, there is minimal research regarding reference diets and no peer reviewed studies with dried distillers’ grains with soluble (DDGS). The objective of this project was evaluating the effect of SoyPlus as a protein supplement in a diet for feedlot goats and substituting ammonium chloride with SoyChlor in high rumen undigestible protein (RUP) feedlot Boer goat diets. Seventy-five Boer-influenced goats were allocated to 5 treatments in a random titration design. Goats were stratified by BW into 25 pens (5 pens/treatment; 3 goats/pen) for a 42-day finishing study. All diets were isonitrogenous and isocaloric, formulated to meet equal daily requirements and equal chloride value. The dietary treatments being evaluated were 1) Soybean meal (SBM) with Ammonium chloride (AmCl), 2) DDGS with AmCl, 3) SoyPlus with AmCl, 4) SBM with SoyChlor, and 5) SoyPlus with SoyChlor. Goats remained on self-feeders with continuous access to their respective pellets and clean, fresh water. Throughout the trial body weight (BW), average daily gain (ADG), average daily feed intake (ADFI), and gain to feed (G:F) were measured and calculated every 7 days. Beginning BW were similar across treatments (P=0.57). The inclusion of SoyPlus and SoyChlor had no effect (P>0.14) on BW or ADFI from day 0 to day 42. Feed Cost $/goat had an increasing cost with increasing inclusion of SoyPlus and SoyChlor. Goats being fed diets containing SoyPlus have a greater feed cost than DDGS of $7.07 (P=0.02). Ultimately, these results confirm that the inclusion of SoyPlus and SoyChlor have no effect on the growth rate of feedlot boar goats. Feeding these diets will mean greater production cost, resulting in the same amount of muscle growth. At these prices, DDGS are the best option when formulating diets and keeping the cost minimal.
Keywords: Fall 2018